The Amá¹¡Äl Method in the Case of Ruâ€™yatullah and Its Implications for Islamic Religious Education - Alamsyah, Adam; Selvia, Sasmi; Sumarna, Elan; Syahidin, Syahidin (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
The learning method of the Prophet Muhammad is full of pedagogical content so it has become a prototype learning method for educators and has provided many positive learning outcomes. This article aims to analyze the amá¹¡Äl method in the authentic BukhÄri hadith number 573 regarding the amá¹¡Äl of the Prophet Muhammad and its implications for Islamic religious education, especially on the theme of monotheism/belief. The author uses a qualitative descriptive approach through literature study to examine theories of research variables from relevant hadith books, books, and journals. The author also uses the takhrij method in terms of both matan and sanad hadith with the help of jawami' al-kalim and al-maktabah al-syamilah as well as a hadith dictionary. Based on takhrij, this hadith is classified as an authentic hadith li zatihi. This hadith includes hadith that is maqbul, ma'mul, and muhkam so it is worthy of being a strong proof to be conveyed to the people. The mass expressed can be categorized as maá¹¡al al al-musarrahah or al-qiyasiyah. The amá¹¡Äl method is effectively applied as a PAI learning method which contains monotheism material. The amá¹¡Äl method is considered capable of realizing education that relies on three main human instruments, namely the heart, mind, and senses. The proverb method is student-centered, where teachers need to accommodate the needs of their students. Ru'yatullah studies provide opportunities for students to develop their theological understanding to create a comprehensive awareness.